Revisiting Educational Pedagogy in Nepalese Legal Education: Post Pandemic Situation - Gautam, Gyanu (Kathmandu School of Law Review, 2024)
This paper examines the educational pedagogy of Nepali legal education from its earliest days to the current post-covid context using empirical research at Tribhuvan University, Purbanchal University, and Mid-Western University. In the light of many philosophical foundations, including cognitive, constructivist, social constructivist, behaviorist, and liberalist approach, the author has studied the pedagogies in lieu with the curriculum, syllabus, course coverage, examination modality, lesson Plan, teaching- learning ecosystem, and application of clinical and practical style of teaching in aforementioned universities. In order to modernize and standardize legal education and develop competent, moral, and accountable legal professionals, Nepal Bar Council has released Legal Education Regulation 2077, which the author has complemented with a critical dissection of its prescriptions on pedagogical aspects. The Covid-19 pandemic-led changes, that floated around the world, have been analyzed in relation to the altered circumstances of contemporary legal education, particularly a paradigm shift that occurred in the law universities by switching its teaching method into online mediums. It is evident that in contrast to Behaviorism, (Social) Constructivism, and Liberalism, which had a trend of imparting legal knowledge practically and clinically, legal education during the Covid era was predominately text-based, carrying the legacy of cognitive approach to teaching. Therefore, it is crucial to make every effort to address the issues that are still present in the post-covid era by carefully revisiting the teaching methodologies of law.